Location Factors of Foreign Direct Investment: A Regional Perspective - Jaworek, Małgorzata; Kuczmarska, Magdalena; Kuzel, Marcin (Olsztyn Economic Journal, 2018)
The following article presents the results of three research projects on foreign direct investment (FDI) in the Kujawsko-Pomorskie Province. They have been conducted by the Nicolaus Copernicus University team in 2003–2004, 2011–2012 and 2014–2016 respectively. The research was carried out using the same research method and covered both local authorities and enterprises with foreign capital operating in the province. The results of these studies allowed the authors to compare the assessments of FDI location factors among both groups of respondents as well as to identify potential changes in their perception over time and to confront these conclusions with the results of other research studies carried out in several other Polish provinces.